Letter (copy) : Spanish Refugee Children - Tewson, Vincent
1940-12-24 038-0038-001 Secretary's. HVT/FC/98. WP/LN/41. 24th December, 1940. Mr. C. Dukes, The National Union of General & Municipal Workers, Woodfield, Copperkins Lane, Amersham, BUCKS. Dear Mr. Dukes, SPANISH REFUGEE CHILDREN. Referring to your letter of the 18th instant enclosing copy of a letter received from your Glasgow District Secretary the Spanish Fund was used to assist Basque children who came to this country during the Spanish war. For eighteen months, however, the money raised has been used for Spanish seamen and has long since been exhausted, but I may say privately that we have earmarked a small sum for the assistance of the Basque Children's Committee if the financial position becomes desperate. As you probably know I am personally interested in the Home at Barnet, but we have not made any grants from our funds to individual Homes. Monies that have been paid over have always been to the Central Committee. At the moment the Central Committee is just managing to pay its way. With all good wishes, Yours sincerely, Assistant Secretary. 292/946/38/38(I)